The ritual - Russell, Bailey J. (Russell, Bailey J. Haunting of Hawthorne Harbor, 2021)
Dan suspects that a ritual involving human sacrifices opens portals to the dead. After three bodies are found near one of them, the Seers launch an investigation into who is performing the rituals.